Wie viel Mathematik gibt es in der Sprache? Interdisziplinäre Zugänge / How much Math is there in the Language? Interdisciplinary Approaches - Joanna Szczęk (Linguistische Treffen in Wrocław, 2024)
In the language of the respective country or language community, many mathematical components can be found, which are often used in the form of stable expressions. They are used in various areas of everyday life, often with different meanings than those primarily attributed to such units. But what is the relationship between language and mathematics? This question is at the forefront of the volume „Mathematics in European Languages. Linguistic Approaches and Interdisciplinary Perspectives“ by Magdalena Lisiecka-Czop and Katarzyna Sztandarska, who has already been published by Vandenhoeck & Ruprecht Verlag. The volume brings together studies in which mathematical terminology and its linguistic relationships are discussed from various perspectives. These are phraseological, lexicographic, lexicological, semantic, pragmatic, semiotic, cognitive, translational and didactically oriented analyses, often contrastive. The volume opens up new interesting research perspectives and raises many questions that will hopefully be answered in further scientific studies inspired by the volume.